FITUR-FITUR PROSODIK DALAM BAHASA MELAYU BANGKA, DIALEK SUNGAILIAT: KAJIAN FONETIK AKUSTIK - Donal Fernado Lubis; Tri Arie Bowo; Mochammad Sultan Zahan; Kevin Georgy Kilen (Universitas Nahdlatul Wathan Mataram, 2024)
The Bangka Malay language, which is a Malay-Polynesian language family, has dialect variations with heterogeneous sub-dialects within it, and one of them is Sungailiat dialect. The purpose of this study is to focus on documenting prosodic features of Sungailiat dialect as one of the dialects in Bangka Malay language. This research is a qualitative research with research stages applying phonetic experiments using a practical phonetic and phonology approaches developed by Collins and Mess (2019). Prosodic features include speech intensity, duration, and intonation. Data collection was carried out through a process of observation, interview, and recording of respondents who are native speakers of the Sungailiat dialect. The data were processed by using voice analyzer software Praat version 6.3.03 to obtain accurate measurements of intensity, duration, and intonation. The results of the analysis show some variations in lexical entries, particularly from the elder informants. Intensity is marked by the oscillation of intensity contours and the frequency densities since the speech flows in co-articulation effect. That means that the adjacent vowels or consonants interchange to form the speech dynamics. Speech intonation in Sungailiat dialect is identical with accentuations of initial syllable, particularly when addressing someone. Imperative mood is prone to be in offering form rather than in command. In speech duration, elder informants are likely to show the whole prosodic variables particularly, as in the flow of their speech in higher pace, and more accented points in intonation contours. Interference of culture in daily communications is believed to shape Sungailiat dialect as it is shown in the prosodic analysis.